2001
DOI: 10.1046/j.1472-765x.2001.00938.x
|View full text |Cite
|
Sign up to set email alerts
|

A microwave-based method for nucleic acid isolation from environmental samples

Abstract: Aims: A simple and rapid method was described for DNA isolation directly from activated sludge or other environmental sources, including soil and sediments. Methods and Results: The present method is based on microwave thermal shock and provides DNA suitable for further analysis. It is also effective for RNA extraction. Conclusions: The protocol is effective, easy, fast and does not require the use of expensive equipment or reagents. Significance and Impact of the Study: The described method can be applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 19 publications
1
62
0
1
Order By: Relevance
“…Other methods, which use mortar mill grinding [64], grinding under liquid nitrogen [73,77], ultrasonication [48,51] and microwave thermal shock [47] have also been reported. Frostegard et al [17] observed that drying soil before grinding greatly improved the lysis efficiency.…”
Section: Cell Lysismentioning
confidence: 99%
See 1 more Smart Citation
“…Other methods, which use mortar mill grinding [64], grinding under liquid nitrogen [73,77], ultrasonication [48,51] and microwave thermal shock [47] have also been reported. Frostegard et al [17] observed that drying soil before grinding greatly improved the lysis efficiency.…”
Section: Cell Lysismentioning
confidence: 99%
“…Another denaturing agent, guanidine isothiocyanate has been used for mRNA extraction from seeded soils [47,71] but has [71] not proven valuable when extracting DNA from soil samples [37,42].…”
Section: Cell Lysismentioning
confidence: 99%
“…The extraction procedure described by Orsini and Romano-Spica avoids the co-purification of humic substances by applying a microwave thermal shock and the addition of polyvinylpyrrolidone at high concentrations [14]. As can be seen in table 1 Many workers have attempted to increase genomic DNA purity and yield from environmental samples by using various kinds of treatments.…”
Section: Resultsmentioning
confidence: 99%
“…The genomic DNA of Thermoactinomyces sp. CDF was extracted according to the method of Orsini & Romano-Spica (2001), except that the cells were disrupted by grinding with a mortar and pestle, rather than microwave treatment. A fragment of the gene (cdf) encoding protease CDF was amplified from the genomic DNA with Pfu DNA polymerase by PCR employing two consensus-degenerate hybrid oligonucleotide primers (CODEHOPs), F and R (Table 1), designed on the basis of two highly conserved amino acid sequences around the catalytic residues His and Ser of subtilases (Wu et al, 2004) ( Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%